48.1k views
4 votes
Write the sum using summation notation, assuming the suggested pattern continues.

-9 - 3 + 3 + 9 + ... + 81

summation of the quantity negative nine plus six n from n equals zero to fifteen
summation of negative fifty four times n from n equals zero to fifteen
summation of negative fifty four times n from n equals zero to infinity
summation of the quantity negative nine plus six n from n equals zero to infinity

1 Answer

6 votes

Answer:

It is the first choice.

Explanation:

This is a sequence where

the next term is obtained by adding 6.

first term = -9 + 6(0) = -9

second term = -9 + 6(1) = -3

third term = -9 + 6(2) = 3

4th term = -9 + 6(3) = 9

and 81 = -9 + (6*15).

So the answer is Sigma (-9 + 6n) from n= 0 to n = 15.

User Takayuki
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.